Phase separation in evaporating all-aqueous sessile drops. Issue 34 (22nd August 2022) - May, Alexander; Hartmann, Johannes; Hardt, Steffen
Abstract : The phase transition and phase distribution in an all-aqueous sessile drop containing polyethylene glycol (PEG) and dextran is studied. Abstract : The phase transition and phase distribution in an all-aqueous sessile drop containing polyethylene glycol (PEG) and dextran is studied. Evaporation of water triggers the formation of dextran-rich droplets close to the contact line of the drop that subsequently migrate towards the drop center. The likely reason for the droplet migration is Marangoni convection due to stresses at the interface between the dextran-rich droplets and the surrounding liquid.